Formation of TiO2 Nanotubular Layers on Ti-6Al-4V Based Dental Implants for Inhibiting Biofilm Growth - Slamet; Bachtiar, Boy M.; Wulan, Praswasti P.D.K.; Aprianto, Billy; Ibadurrohman, Muhammad (Asian Journal of Chemistry, 2020)
Modification of Ti-6Al-4V through electrochemical anodization method has been investigated on the purpose of generating TiO2 nanotube arrays (TiNTAs) on the surface of Ti-6Al-4V films. The as-anodized samples were calcined in an atmospheric furnace at various temperatures, in the range of 500-800 ºC. The evaluation of biofilm inhibition was performed by an in vitro method with Streptococcus mutans as a bacterium model. FE-SEM imaging confirmed the successful formation of TiO2 nanotube arrays while XRD results implied a phase transformation from anatase to rutile when the calcination temperature was around 600-650 ºC with average crystallite size of 18 nm. Calcination temperature is one of determining factors in the adjustment of crystallinity and morphology of TiO2, which in turn affects its capability to suppress biofilm formation. This study revealed that the best sample for biofilm inhibition was calcined at 600 ºC with a crystallite phase of mostly anatase. This sample managed to improve antibacterial activity of up to five times as compared to the unmodified Ti-6Al-4V. The output of this study is expected to give some insight on a promising alternative for preventing the formation of harmful biofilm on dental implants.